2018
DOI: 10.15419/jmri.111
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Profile of Spinal Cord Injury Patients Admitted in a Rehabilitation Centre: An Observational Study from Bangladesh

Abstract: Background:  Spinal cord injury (SCI) is a life threating condition which has a profound impact in the morbidity and mortality. SCI causes lifetime sufferings and mostly occur among the young adults. Not only in Bangladesh but also worldwide, SCI is a devastating and burdensome condition. This research was conducted to see the demographic profile of SCI patients in Bangladesh. Methods and Materials: This is a retrospective analysis where data was collected from medical records of all SCI patients admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Purposive sampling techniques were conducted to achieve a range of participants varying in age, gender, marital status, onset and causes of injury, and geographical locations. Research participants' demographics were matched with the national and CRP SCI demographics [ 31 ]. In Bangladesh, the sex ratio between males and females with spinal cord injury is 4.5 : 1, and the mean age of injury is 34.5 years, which is different from Western literature [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Purposive sampling techniques were conducted to achieve a range of participants varying in age, gender, marital status, onset and causes of injury, and geographical locations. Research participants' demographics were matched with the national and CRP SCI demographics [ 31 ]. In Bangladesh, the sex ratio between males and females with spinal cord injury is 4.5 : 1, and the mean age of injury is 34.5 years, which is different from Western literature [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…34 Severe injuries, like head or spinal cord injury, also crippled a substantial number of RTC victims. [35][36][37][38] In a tertiary hospital, it was found that RTC was responsible for 80% of spinal injury patients with multiple injuries. 39 Among the patients with a pelvic fracture at 2 tertiary hospitals in Dhaka, RTC was the major cause.…”
Section: Characteristics Of Rtcsmentioning
confidence: 99%
“…The most common causes of traumatic spinal cord injury (T-SCI) around the world and as well in Pakistan are falls from height, road/traffic accidents, gunshot injuries or sport accidents 4 . Moreover, there are a number of medical conditions (degenerative disc disease, tumors) that are responsible for non-traumatic spinal cord injury (NT-SCI) 5 .…”
Section: Introductionmentioning
confidence: 99%